Urinary Neutrophil Gelatinase-Associated Lipocalin, Cystatin C and Clusterin as Biomarkers for Acute Kidney Injury in Cattle with Tropical Theileriosis - Tumer, Kenan Cagri; Dincer, Pelin Fatos Polat; Babacan, Sumeyye; Yerlikaya, Zeynep (Univ Agriculture, Fac Veterinary Science, 2023)
Schizont-infected nucleated cells and anemia-induced hypoxia may cause acute kidney injury (AKI) in cattle with tropical theileriosis. In most cases, serum creatinine (sCr) fails to detect early kidney injury. Recently, urine biomarkers such as neutrophil gelatinase-associated lipocalin (NGAL), Cystatin C (CysC), and Clusterin (Clu) have outperformed sCr in identifying AKI in various animal species. However, these markers have not been tested in cattle for AKI detection. This study investigated AKI in cattle with tropical theileriosis using serum and urinary NGAL, CysC, and Clu and compared them to standard renal function markers such as sCr, urine protein to creatinine (uPC) ratio and urine-specific gravity (USG). Seventeen cattle were infected with Theileria annulata (Th) and ten were controls (CTRL) in this investigation. The urinary NGAL (uNGAL) in the Th group was considerably (P<0.001) greater than that in the CTRL group. uCysC increased significantly in the Th group compared to CTRL group (P<0.001). The Th group had higher sClu than the CTRL group (P<0.001). There was a significant difference (p=0.005) in sCr concentrations between Th and CTRL groups, but the values were within the reference range in both groups. Th group had a higher uPC ratio than CTRL (p= 0.002), whereas USG was lower in Th group than in CTRL group (P<0.001). These results suggested that cattle with tropical Theileriosis have acute tubular injury.
Keywords: Clusterin; Creatinine; Cystatin; Neutrophil gelatinase-associated lipocalin; Theileria annulata; Tubular injury